Phytochemical and Biological Activities of Four Wild Medicinal Plants - Anwar Ali Shad; Shabir Ahmad; Riaz Ullah; Naser M. AbdEl-Salam; H. Fouad; Najeeb Ur Rehman; Hidayat Hussain; Wajid Saeed (The Scientific World Journal)
The fruits of four wild plants, namely, Capparis decidua, Ficus carica, Syzygium cumini, and Ziziphus jujuba, are separately used as traditional dietary and remedial agents in remote areas of Khyber Pakhtunkhwa, Pakistan. The results of our study on these four plants revealed that the examined fruits were a valuable source of nutraceuticals and exhibited good level of antimicrobial activity. The fruits of these four investigated plants are promising source of polyphenols, flavonoids, alkaloids, terpenoids, and saponins. These four plants' fruits are good sources of iron, zinc, copper, manganese, selenium, and chromium. It was also observed that these fruits are potential source of antioxidant agent and the possible reason could be that these samples had good amount of phytochemicals. Hence, the proper propagation, conservation, and chemical investigation are recommended so that these fruits should be incorporated for the eradication of food and health related problems.